Previous Exposure to Literature Studies and Trainings in English Language Teaching for Literature: A Survey on Their Effects on the Teaching of Literature in the ESL Classroom - Chong, Siaw We (Universiti Malaysia Sarawak (UNIMAS), 2005)
This project sought to investigate on the efficacy of literature studies and English Language Teaching for Literature in bridging teachers' knowledge gap regarding the teaching of literature as well as in enhancing teachers' teaching practices in the ESI, classroom. It also aimed to find out on teachers' needs towards future enhancement programmes in the teaching of literature. One hundred and twenty one teachers were involved in this project. The instrument used for data collection was questionnaire. The data was recorded, calculated and analyzed descriptively. The findings of this project revealed that teachers' previous exposure to literature studies and English Language Teaching for Literature is effective in bridging teachers' knowledge gap such as providing them with knowledge on literary elements in literary texts, knowledge regarding cultural elements in prescribed texts, knowledge in terms of methodology in the teaching of literature, knowledge on the role that literature teachers should play regarding students' response to texts, and knowledge regarding the role that literature teachers should demonstrate in their own response to texts. Teachers' previous exposure to literature studies and English Language Teaching for Literature is also effective in enhancing teachers' teaching practices in the ESL classroom. This can be seen from respondents' ability to put into practice their knowledge regarding the teaching of literature as well as to demonstrate the roles that a literature teacher should play, such as being able to choose appropriate methodology in the teaching of literature, able to teach cultural elements in prescribed texts, able to make students engage with texts, able to help students develop their responses towards the texts, able to demonstrate their response on texts to students, able to select, adapt as well as create materials regarding the teaching of literature. As for teachers' needs for future enhancement programmes with regards to English Language Teaching in literature, the teachers researched chose teacher-support and teaching material, workshops and hands-on experiences as well as short-term in-service courses.